RANCANG BANGUN SABLON JALUR LAYOUT PCB OTOMATIS BERBASIS PROGRAMMABLE LOGIC CONTROL (PLC) - Irawati Irawati; Deasy Kartikasari; Karyadi Karyadi (Institut Teknologi dan Bisnis Swadharma, 2022)
Advances technology in life is also accompanied by innovations from various automation processes, a strong reason that encourages the formation of this PLC-Based Automatic PCB Path Screen Printing tool, starting from students printing PCB by ironing the circuit design results on the PCB, which takes time long enough. At this step, many people experience problems, including the paths on the PCB etching results are broken due to the uneven ironing of the printed results. As a result, the circuit does not work as intended. Therefore, a PCB etching machine is needed that can work automatically. It can produce the desired circuit results in a shorter and better time, The way this PCB screen printing machine works, is to use a Heater (heat element), which is then controlled by the Thermo Controller, and programmed by the PLC, and pushes and pressing using air pressure (pneumatic) which is then determined by the Timer, During the specified time, After finishing the PCB screen printing results are cooled by a 24v DC fan, this tool has specifications with a length of 60cm, width 40cm and height 80cm this machine is designed to minimize time and effort to be faster and get better results